Effect of asking questions and providing knowledge on attitudes toward organic foods among Japanese consumers - Iwatani, Shuma; Honda, Hidehito; Otaki, Yurina; Ueda, Kazuhiro (Frontiers in Psychology, 2023)
Some people overestimate the benefits of certain kinds of foods, such as organic foods, while others underestimate it. Previous studies have found that reducing people's self-assessed knowledge successfully moderated these extreme attitudes. In this study, we investigated interventions to reduce people's self-assessed knowledge and to moderate attitude extremity. We examined extreme attitudes toward organic foods and investigated the effects of implementing two intervention methods to moderate their attitude: (1) providing knowledge on organic food after asking them some questions and (2) simply providing them with knowledge. We conducted a two-factor mixed-design experiment with 653 college-educated Japanese women. In the first condition, before knowledge provision, participants were asked to answer questions about organic foods and were then informed of the correct answer and whether their answer was correct (Q&A Intervention). This step was based on an intervention conducted in a previous study to reduce their self-assessed factual knowledge. In the second condition, participants were simply provided with knowledge without being asked to answer any questions (Simple Intervention). The results showed that both intervention methods, on average, decreased the participants' self-assessed knowledge and attitude extremity. Therefore, simply 2 This is a provisional file, not the final typeset article providing knowledge may be effective in reducing their self-assessed factual knowledge and moderating their extreme attitudes toward organic foods.